Pengembangan Evaluasi Media Slide Berbasis Aplikasi Physics Education Technology (PhET) dalam Meningkatkan Eksplorasi Aktif dan Kreasi Materi Listrik - Syahrina, Aulia; Yovita, Yovita; Syafiuddin, Fauzan Azima (Mitra PGMI: Jurnal Kependidikan MI, 2024)
The aim of this research is to enhance students' understanding in the subject of Science and develop their practical skills. The study assesses the role of educators in designing and effectively delivering this integrated curriculum, emphasizing the importance of an interdisciplinary approach. Furthermore, the research evaluates the curriculum's impact on students' learning outcomes and their engagement in the subjects of Science and electrical installations. The Research and Development (RnD) method, specifically field research, was employed, utilizing literature sources from books and journals. Data collection involved interviewing 28 students as the sample. Validation analysis indicates that the learning media is highly rated by teachers for content suitability, presentation quality, user-friendliness, alignment with objectives, and teaching effectiveness, with scores ranging from 9.1/10 to 9.6/10. Students also provided positive assessments, albeit slightly lower, with average scores ranging from 8.4/10 to 8.9/10. Overall, the learning media is considered valid and effective in enhancing understanding of electrical installation materials. Practicality assessments regarding validity show that teachers and students rated the learning media highly in all aspects, indicating high consistency in media quality. Despite minor differences in opinions between teachers and students, both generally acknowledge the quality of the learning media.